leadership and IWB The Effect of Transformational Leadership, Organizational Support, Knowledge Sharing and Engagement to Innovative Work Behavior of Teachers At Private Shipping Vocational Schools In Jakarta - Mutia, Nila (JERAM, 2017)
The objective of this research is to study the effect of the transformational leadership, organizational support, knowledge sharing and employee Engagement to innovative work behavior of teachers at private shipping vocational schools in Jakarta. Quantitative Method was used in this research as well as Survey Method. The samples of this research were one hundred and twenty three teachers selected randomly out of one hundred and sixty five teachers. The data were obtained by distributing questionnaires and were analyzed by using the path analysis. It can be concluded from the result of the research that: 1) the transformational leadership, organizational support and employee Engagement had a direct positive effect on innovative work behavior; 2) the transformational leadership, knowledge sharing and organizational support had a direct positive effect on employee Engagement; and 3) the transformational leadership and organizational support had a direct positive effect on knowledge sharing. Therefore, to improve innovative work behavior of teachers, the transformational leadership, organizational support and employee Engagement should be improved.